Quality Dahi Preparation in Automated Controlled Ambient Conditions - Chitranayak; Jaiswal, Premkumar; Minz, P. S.; Vairat, Amita D.; Kumari, Khushbu; Raju, P. N. (International Journal of Bio-resource and Stress Management, 2021)
This automated controlled system eliminates the need of two separate places for incubation of the curd at higher temperature in the range of 39 to 43°C and then shifting the set curd cups into cold rooms for storage purpose and kept at about 4 to 5°C.The transient cooling process of dahi, set in cups and also in steel containers placed in cold air flow was conducted in this experimental study. Recording of the temperature of dahi-cups and of the supplied air were done at regular intervals until the temperature reached below 4°C to 5°C. The exponential curves of cooling by forced convection process for the dimensionless temperature of curd were obtained for the trials conducted at the different velocities of cooling air flow. It was found that the surface heat transfer coefficient increased and duration of cooling decreased by increasing the air velocities from 0.5 m/s by evaluating the Biot number and surface heat transfer coefficient. In the initial period of cooling this pattern was more effective and reduced for higher velocities of air from 3.5 to 4.5 m/s. The method of incubation and storing dahi-cups at the same place and changing the ambient temperature of the whole environment instead of changing the place of dahi-cups for cooling purpose have been applied in this research work to control the problem of whey-off in set-curd.